Evolution of the Global Fitness Industry : Strategy, Sustainability and Innovation. - Gazzola, Patrizia (Routledge, 2024)
The pandemic has taught us all how important it can be to look after our physical and mental health, and how worthwhile it is to invest in taking care of ourselves. This short book illustrates the main trends that are modifying the fitness industry worldwide and highlights contemporary relevance to strategic change. It outlines what is currently happening within the promising fitness market and analyses the major emerging trends and the scientific data, referring to startups that could become very interesting market players in the years to come. Sustainability and technology will be the subject of in-depth analysis, as they represent the main drivers that will guide the sector in the future. The book also considers the most important aspect of sustainability related to the fitness industry and wellness more generally: the Silver Economy. The analysis is supported by an extensive database involving the 100 leading companies in the sector worldwide. The novelty of this research is to provide a document analysing the typical characteristics of this market, consumption dynamics, consumer triggers, and underlying the socio-economic scenario. The treatment of key themes such as fitness-tech startups, sport strategic management and above all innovation and sustainability make the book unique and appealing to researchers, academics, students, and practitioners.
Keywords: Physical fitness centers.; Sporting goods industry.; Sport clothes industry.; elektronické knihy; electronic books